The Impact of The Skilled Workforce on The Entrepreneurial Environment in The South – East Region - Daniela Lavinia BALASAN; Florin Marian BUHOCIU; Silvius STANCIU; Laura Delia ANGHELUȚĂ (Communications of International Proceedings, 2021)
The analysis of economic development refers to the increase of the standard of living and the prosperity of the population. The labour force reports key data on the development capacity of the economy, the level of economic and social growth, as well as the potential attractiveness of the Region. In this paper, important tools of labour dynamics were discussed, inspiring the attractiveness of investment and labour productivity, such as the working population, the inactive population, the degree of training of the inhabitants, but also the entrepreneurial environment and what it entails. If it could be exploited effectively, the South-East Region can enjoy real development potential, which ranks it among the first regions in our country. The lack of skilled labour in the region is a major problem.
Keywords: development; rural potential; indicators; labour force.